Asthidhatu Kshaya and Osteoporosis: A Comprehensive Review of Ayurvedic and Modern Perspectives (AYUSHDHARA, 2025)
Asthidhatu Kshaya, a condition described in Ayurveda, exhibits similarities with osteoporosis in modern medicine. This review aims to provide a comprehensive comparison of these conditions, analyzing their pathophysiology, etiology, symptoms, diagnostic methods, and treatment approaches. Osteoporosis, a major public health concern, is associated with increased fracture risk and reduced quality of life, particularly in aging populations. Ayurveda offers a unique perspective on bone health, emphasizing balance in bodily humors (Doshas) and metabolic factors influencing bone tissue formation and degeneration. Understanding the correlation between Asthidhatu Kshaya and osteoporosis through an integrative lens may contribute to the development of more holistic, individualized, and preventive treatment strategies. Additionally, this review highlights the potential of combining traditional Ayurvedic wisdom with modern scientific advancements to optimize bone health management and improve patient outcomes.